Evaluation of a proper cutoff value on quantitative dual-energy perfusion CT for the assessment of acute pulmonary thromboembolism. (September 2017) - Kunihiro, Yoshie; Okada, Munemasa; Matsunaga, Naofumi
Background: The cutoff value for assessing the severity of acute pulmonary thromboembolism (PTE) using relative volumetric evaluations of dual-energy perfusion computed tomography (DEpCT) is unclear. Purpose: To determine the proper cutoff value for determining the severity of PTE using DEpCT volumetry. Material and Methods: A total of 185 patients with venous thromboembolism were included in this study, of whom 61 were diagnosed with acute PTE. DEpCT images were three-dimensionally reconstructed at the following attenuation ranges: 1–2 HU (V2), 1–10 HU (V10), and 1–120 HU (V120). The ratios of low perfusion areas associated with each threshold range per V120 were also calculated, and the relative ratios were expressed as %V2 to %V10. These values were compared with factors indicating the severity of PTE, including the pulmonary arterial pressure, heart rate, CT angiographic obstruction index (CTOI), and right/left ventricular diameter ratio (RV/LV). Results: The area under the curve (AUC) of %V2 was highest (0.783) among these values (95% confidence interval, 0.710–0.856) based on the presence of IPCs. The %V2 showed moderate correlations with CTOI (r = 0.36, P = 0.005) and RV/LV (r = 0.36, P = 0.004) in the patients with acute PTE. Conclusion: Volumetric evaluations of DEpCT images using the lowest attenuation threshold range (1–2 HU) exhibit the best correlation with factors suggesting the severity of acute PTE.